Endocarditis‐induced thrombotic thrombocytopenic purpura mimicking preeclampsia: A case report - Abdulmoez Issa; Moudar Kouli; Randa Awwameh; Lugien Alasadi; Ali Alrstom; Omar Arssan Alshadid; Tamim Alsuliman; Ameen Sulaiman (Clinical Case Reports, 2021)
Abstract TTP, Preeclampsia have similar manifestations in pregnancy. Establishing the right diagnosis is essential as the treatment is different. Endocarditis‐induced TTP should be suspected when neurological symptoms, thrombocytopenia are present.